The Self-Esteem Paradox in Communication Privacy Management of Body-Shaming Victims on Social Media - Ainal Fitri; Astia Maulida; Fathayatul Husna; Muhammad Haekal (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2026)
Body shaming on social media is an increasingly prevalent phenomenon alongside high social media penetration in Indonesia, yet discussions on victims’ management of their communication privacy following traumatic experiences remains limited. This study explores interpersonal communication privacy management strategies of body shaming victims using the Communication Privacy Management (CPM) Theory. Through a qualitative descriptive approach involving five university students who experienced body shaming across social media platforms, this research reveals a self-esteem paradox phenomenon in digital privacy management contexts. The findings demonstrate three main discoveries. First, self-esteem levels significantly determine privacy management strategies developed by victims. High self-esteem does not automatically produce adaptive strategies, but is mediated by privacy turbulence severity, social support, and self-awareness. Informants with high self-esteem may exhibit maladaptive strategies such as extreme isolation, while those with low self-esteem can develop more adaptive strategies through self-acceptance. Second, coping mechanisms developed by victims are essentially manifestations of CPM strategies, showing that in digital trauma contexts, both are two sides of the same coin. Third, cultural contexts with strong Islamic values and customary traditions shape how victims develop privacy rules and boundary regulation. These findings contribute theoretically to CPM literature by highlighting the need for multi-platform and cross-cultural dimensions in privacy management frameworks, and practically by informing the development of culturally sensitive digital literacy interventions for body shaming victims